Innovative approaches in bioremediation: the role of halophilic microorganisms in mitigating hydrocarbons, toxic metals, and microplastics in hypersaline environments - Zeinab Rezaei; Mohammad Ali Amoozegar; Hamid Moghimi (Microbial Cell Factories)
Abstract Hypersaline environments are ecologically, industrially, and scientifically important because they host unique extremophiles used in biotechnology, bioremediation, and enzyme production. These habitats are seriously threatened by three common contaminants: hydrocarbon pollutants, toxic metals, and microplastics. In particular, the remediation of hazardous substances under extreme conditions is challenging due to limited accessibility and bioavailability of pollutants, harsh physicochemical conditions, reduced microbial abundance and diversity, and instability of enzymes. Halophiles are extremophilic microorganisms that thrive in high-salt environments, exhibiting notable metabolic diversity and resilience, and play a critical role in overcoming these challenges. Their ability to degrade recalcitrant pollutants makes them valuable for bioremediation in contaminated hypersaline ecosystems. Advancements in engineering tools and synthetic biology have revolutionized halophile-based biotechnologies. Techniques like gene editing and recombinant DNA have facilitated the precise modification of halophiles, enabling them to efficiently target and degrade toxic compounds and significantly improve their bioremediation potential. Furthermore, with the rapid progress of omics approaches, identifying new halophilic microbes, their enzymes, and their metabolic pathways is now becoming possible. Despite these advances, challenges remain in optimizing genetically tractable strains, ensuring biosafety, and understanding microbial ecology for scalable, safe, and cost-effective applications. This review provides an overview of halophilic and halotolerant microorganisms, their habitat, and their unique adaptations to saline and hypersaline environments. Key pollutants threatening extreme environments, as well as the ability of halophiles to degrade them, are also discussed. Additionally, it highlights current challenges, including the introduction of engineered halophiles into natural ecosystems, scaling up bioprocesses, cost management, and regulatory concerns, and explains future perspectives to address these issues. Ultimately, it emphasizes the need for advanced research to fully harness the potential of halophiles in sustainable bioremediation. Graphical abstract